A vision-based dual-modal system for adjusting the orientation and plant spacing of ginger with biharmonic depth completion and rapid hand–eye calibration - Shuxiang He; Lin Liu; Yihe Zhang; Jin Cheng; Yuhua Li; Jialin Hou; Rui Hou; Kai Zhou (Computers and Electronics in Agriculture, 2026)

Fabrication of food-derived bigels beads for the co-delivery of hydrophobic and hydrophilic bioactives: insights into environmental responsiveness and release mechanisms - Rongrong Zhang; Rui Fan; Kai Qi; Jinchi Jiang; Mingzhou Yu; Yiyang Yu; Wenge Yang; Wenhui Li; Yonghong Hu (Food Research International, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Accumulation of hydrophobic bile acids mediates chronic heat stress-induced liver-gut axis injury in spotted seabass (Lateolabrax maculatus) - Fan-bo Yang; Xue-shan Li; Kai Song; Ling Wang; Rui-juan Ma; Kang-le Lu; Chun-xiao Zhang (Aquaculture, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Ultrasonic torsional wave excitation using a double-layer flexible magnetostrictive transducer for HDPE pipe monitoring - Kai Wang; Yizhou Guo; Yini Song; Yiru Xiao; Rui Zhang (Engineering Structures, 2026)

From fermentation to function: a critical review of lactic acid bacteria redesign for functional foods and precision nutrition - Jianwei Zang; Luyao Xiao; Xiaogan Zhao; Yibo Shi; Kai Ma; Changliang Zhang; Shuo Geng; Xin Rui; Tao Lin; Wei Li (Critical Reviews in Food Science and Nutrition, 2026)

Microplastic pollution in an anthropogenically modified river: sediment occurrence, associated microbiota, and environmental correlates - Kai Zhang; Ge Ma; Qingyi Wang; Chengshi Ding; Xinlu Shen; Chaoyue Zhao; Siwei Gao; Chenyang Shen; Hui Gao; Rui Xin; Fengxia Yang (Environmental Monitoring and Assessment, 2026)

Thermo-mechanical damage characteristics and fracture behavior of backfill bodies in thermal energy storage cavities: An experimental and numerical study - Huicong Xu; Kai Li; Bo Zhang; Rui Zhan; Shangtong Yang; Xun Xi; Lianpeng Dai (Tunnelling and Underground Space Technology, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Optimizing spatially non-uniform skylights for museum galleries: Balancing visual quality, artifact conservation, and geometric complexity - Kai Li; Hiroatsu Fukuda; Li Zhang; Rui Zhou (Building and Environment, 2026)

Change of aerosol properties and transport mechanisms in Beijing during 2021-2024 - Rui Xu; Linlu Mei; Kai Ji; Gerrit de Leeuw; Zhibin Lai; Feiyang Wang; Yongliang Yang; Xinhong Zhang; Ruilai Nie (Atmospheric Pollution Research, 2026)

Inhalable HUCMSC-Lipo biomimetic formulation inhibits fibroblast activation in mouse and non-human primate pulmonary fibrosis models - Fangyu Zhao; Yige Sun; Haoran Wang; Dayong Hou; Rui Zhang; Wenjing Xia; Yongchen Zhang; Luyao Li; Xueqi Zhao; Kaiqi Wang; Wenwen Pan; Jiannan Wang; et al. (Science Bulletin, 2026)

Enhanced water level fluctuations reduced the competitive advantage of cyanobacteria - Yan Chen; Rui Xia; Ruining Jia; Junde Ming; Kai Zhang; Jinghui Dou; Tianxiang Zhao; Xiang Li; Qin Zhang; Qi Zhang (Journal of Hydrology, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

From microstructural features to macroscopic properties: A multi-scale investigation on starch characteristics of global potato (Solanum tuberosum L.) germplasm resources - Kai Zhang; Yan Gao; Xiyue Ran; Huajian Xu; Yizhi Du; Mingren Yang; Ruijiang Chen; Rui Jiang; Yong Zhao; Shahid Ullah Khan; Binjia Zhang; Dianqiu Lv (Food Chemistry, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

MS-R outperforms RGB: Lightweight CYOLO-BiCNet enables efficient detection and storage optimization of cotton flowers - Mian Chen; Kai Ma; Xiaoli Geng; Daowu Hu; ShuaiPeng Fei; Shoupu He; Xiongming Du; Meiyan Shu; Shunfu Xiao; Rui Zhang; Yuntao Ma (Precision Agriculture, 2026)

A voyage-level threshold analysis of planned turnaround vulnerability in cruise ports from an AIS big data perspective - Shengjun Gan; Shikai Hu; Han Zhang; Kai Luo; Rui Yang; Salvatore Antonio Biancardo (Frontiers in Marine Science, 2026)
Introduction Cruise port operations are facing increasingly significant challenges in departure reliability amid frequent climate variability, port congestion, supply chain disruptions, and geopolitical risks. Unlike existing studies that mainly explain cruise delays from the perspectives of weather conditions, external shocks, or supply chain risks, this paper focuses on whether port turnaround planning itself may constitute an endogenous source of vulnerability. Methods To identify this issue, this study uses the daily AIS data for the United States released by Marine Cadastre. These data are combined with planned berthing information, weather data, and vessel characteristics to construct a sample of 3,238 cruise ship–port–day observations. The study defines planned turnaround time as a time-based buffer resource in voyage-level operations. It then applies a fixed effects model, a threshold regression model, a half-hour interval model, mechanism tests, heterogeneity analysis, and moderation analysis to systematically examine the impact of planned turnaround time on departure reliability and its operational boundaries. Results The results show a significant threshold-type nonlinear relationship between planned turnaround time and departure delay. An 8.5-hour threshold is identified as the main data-driven cutoff, while a meaningful buffering effect is mainly observed within 8 hours. The interval of 8.0–8.5 hours is better viewed as a transition range where marginal benefits begin to decline. Mechanism tests indicate that actual berthing service time is the most stable primary transmission channel of planned turnaround vulnerability, while port queuing pressure and berth occupancy pressure further modify the marginal effect of planned turnaround time. Discussion This study moves the analysis of cruise departure delays from explanations based on exogenous shocks to the identification of endogenous vulnerability. By revealing that planned turnaround time itself can become a source of risk under specific threshold conditions, these findings complement existing resilience literature that has primarily focused on external drivers. It provides new micro-level evidence for understanding the resilience of cruise port operations, optimizing schedule planning, and improving port coordination efficiency.

Classification of SARS-CoV-2 Variants Through the Epistatic Circos Plots with Convolutional Neural Networks - Bo Jing; Kai-Rui Zhang; Hong-Li Zeng; Erik Aurell (Journal of Molecular Evolution, 2026)
The COVID-19 pandemic has profoundly affected global health, driven by the remarkable transmissibility and mutational adaptability of the SARS-CoV-2 virus. Although five variants of concern, Alpha, Beta, Gamma, Delta, and Omicron, have been identified, the classification task in this study is formulated using four classes: Alpha, Delta, Omicron, and Else, reflecting the sequence availability and temporal coverage of the dataset. Here, we develop an integrative framework that combines direct coupling analysis (DCA), Circos-based visualization, and convolutional neural networks (CNNs) to characterize lineage-specific epistatic signatures from large-scale SARS-CoV-2 genomic sequences. DCA-inferred pairwise mutational couplings were transformed into Circos images, which were then used as inputs for CNN-based classification models. The proposed framework achieved robust variant classification, with the best-performing model reaching a weighted-average $$F_1\text {-score}$$ of $$98.68± 0.75%$$ and an AUC close to 1. Additional temporal holdout analyses showed that the framework retained reasonable predictive capability across evolutionary time, yielding a weighted-average $$F_1\text {-score}$$ of 87.85%.

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Health risk assessment of metal(loid)s in the topsoils of an operating industrial park based on bioaccessibility and quantitative source apportionment - Yiwei Gong; Kaiming Yang; Weici Quan; Jiawen Zhang; Yuxi Wu; Rui Wang; Yadi Ai; Kai Yang; Hongguang Cheng (Journal of Environmental Sciences, 2026)

Investigating stress evolution in rock burst prone regions in an underground mine with seismic tomographic imaging - Xu Ma; Rui Ma; Erik Westman; Baisheng Nie; Miao Zhang; Kai Guo (Geomechanics for Energy and the Environment, 2026)

Drought Duration Alters the Soil Water Threshold Corresponding to the Leaf Photosynthetic Efficiency of Potato in Semi-arid Regions - Yang Yang; Hong Zhao; Shi-qiong Yang; Di-hua Cai; Kai Zhang; Yu-rui Tang; Yue Qi; Peng-cheng Huang (Potato Research, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

CTF-TL: Coarse-to-Fine temporal localization framework for precise recognition of posture transition behaviors in periparturient sows - Zikang Chen; Yan Luo; Chao Yuan; Kai Yan; Rui Diao; Jiachao Zhang; Mingxia Shen; Xiangbo Shu; Xingjian Gu; Mingzhou Lu (Computers and Electronics in Agriculture, 2026)

Corrigendum to “Flow backward alleviated the river algal blooms” [Volume 245, 15 October 2023, 120593] - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2026)

Extreme rainfall intensifies nitrogen responses through baseflow in arid and semi-arid river basins - Jinghui Dou; Rui Xia; Zixuan Tang; Zhen Huang; Xiaohui Jiang; Kai Zhang; Lina Li; Chao Yan (Journal of Hydrology, 2026)

Co-fermentation with autochthonous Levilactobacillus brevis and Lactiplantibacillus plantarum modulates metabolome and volatile profiles to improve the quality and safety of fermented chopped chili - Wenkai Jiang; Qian Yang; Luyao Xiao; Xia Fan; Menghan Zhong; Mahsa Ghahvechi Chaeipeima; Kai Ma; Changliang Zhang; Xin Rui; Wei Li (Food Research International, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

Performance enhancement of alkali-activated slag via in situ CO2 mineralization - Gao Rui; Xu Bingqi; Gao Weichen; Jiang Ping; Zhang Shiyu; Cui Kai; Zhao Yingliang (Sustainable Chemistry and Pharmacy, 2026)

Editor's note “Phosphorus – the main limiting factor in riverine ecosystems in China” [Sci. Total Environ. 870 (2023) 161613] - Yan Chen; Jie Chen; Rui Xia; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Bimetallic sulfide catalysts photocatalytically reduce carbon dioxide into high-value fuels: A review - Chenyue Hua; Kai Xie; Cheng Peng; Jiang Wu; Sheng Wang; Jingxin Xu; Kai Huang; Xueli Sun; Hai Zhang; Rui Zhu; Ping He; Ahmad Hosseini-Bandegharaei (Journal of Environmental Chemical Engineering, 2026)

Paper garland-inspired 2D single-phase spiral folded-rod elastic metamaterial for extremely low-frequency vibration isolation - Kai Miao; Leilei Wang; Wencheng Yin; Rui Zhang; Shuyuan Liu; Facheng Song; Jian Zhu; Lingling Wu; Jianhui Liang; Dichen Li; Ling Wang (Engineering Structures, 2026)

Advances and challenges in multi‑scale water environment system modeling: from process simulation to a novel simulator architecture - Rui Xia; Sheng Chen; Yan Ding; Mingdong Sun; Yali Wu; Kaifang Shi; Yajing Cai; Kai Zhang; Yan Chen; Lei Zou (Ecological Modelling, 2026)

Effects of short-term grazing prohibition on methane, nitrous oxide and nitric oxide fluxes from alpine meadows on eastern Tibetan Plateau - Xiao Chen; Rui Wang; Lei Ma; Han Zhang; Zhisheng Yao; Kai Wang; Wei Zhang; Siqi Li; Shenghui Han; Chunyan Liu; Yong Li; Xunhua Zheng (Agriculture, Ecosystems & Environment, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Mitochondrial Genome and Phylogenetic Analysis of Rhinogobius virgigena - Yi-Jing Zhan; Wei Hu; Kai-Rui Zhang; Cheng-He Sun (Biochemical Genetics, 2026)

Application of GA-SA Optimization Algorithm with Two-Level Precision Control in Inversion - Rui-qing Hu; Kai Gao; Lu Yu; Yi-Ming Zhang; Qing Li; Jie Meng (Applied Geophysics, 2026)

Evaluating the environmental impact of hydrothermal cracking solid organic fertilizer: Carbon and nitrogen retention and toxic metals analysis - Rui Xia; Xiao-xiao Yang; Jue Wang; Kai-le Li; Zhi-peng Sun; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Journal of Environmental Sciences, 2026)

How biodegradable mulching alters soil nitrogen transformations to enhance soil nitrogen supply and influence gas emissions in a maize cropping system - Hao Zhang; Kai Wang; Jinbo Zhang; Christoph Müller; Dianyuan Ding; Qiang Li; Hengliang Tang; Rui Jiang (Plant and Soil, 2026)

Scalable phenotyping and yield estimation via stability index and single-plant variability using a vision-based large model framework - Mian Chen; Guangyao Sun; Kai Ma; Xiaoli Geng; Daowu Hu; ShuaiPeng Fei; Xiongming Du; Shoupu He; Rui Zhang; Shunfu Xiao; Lei Meng; Yuntao Ma (Computers and Electronics in Agriculture, 2026)

A multi-layer coupling framework for hydrodynamic simulation of underground station flooding - Dong-Mei Zhang; Hai-Yun Li; Wen-Ding Zhou; Si-Rui Chen; Zhong-Kai Huang (Tunnelling and Underground Space Technology, 2026)

QuaFT: Quality-guided semantic fault intelligence under corrupted industrial data - Lu Ning; Rui Wang; Xiaoran Wei; Hao Huang; Zonghan Zhang; Zehua Chen; Xiaolu Liu; Bo Zhang; Yao Liu; Hao Gong; Kai Song (Process Safety and Environmental Protection, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Understanding the migration and transformation characteristics of Cr3+ in the hydrothermal cracking of biomass model components - Rui Xia; Kai-le Li; Peng Zhao; Xiao-xiao Yang; Jue Wang; Ke-wen An; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Biomass and Bioenergy, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Warming and precipitation alter soil viral community structure and functional characteristics in dryland wheat fields on the Loess Plateau, China - Jin Kou; Feiyan Zheng; Jiaxuan Lei; Ting Wang; Heling Wang; Kai Zhang; Rui Tian; Xiaodong Lyu (Plant and Soil, 2026)

Three-Dimensional Analysis of Shield Tunnel Face Stability Using Adaptive Lower Bound Finite Element Limit Analysis with the Drucker–Prager Criterion - Rui Sun; Kai Zhang; Haibing Cai (Geotechnical and Geological Engineering, 2026)

Navigational path optimization methodology for wing-diesel hybrid ship based on improved Double Deep Q-Network - Cong Wang; Lianzhong Huang; Ranqi Ma; Kai Wang; Jinlu Sheng; Zhang Ruan; Rui Zhang; JianLin Cao (Ocean Engineering, 2025)

The effect of minimum temperatures on changes in river dissolved oxygen is more pronounced in the climate transition zone - Qin Zhang; Rui Xia; Kai Zhang; Haiming Li; Yan Chen; Ruining Jia; Jinghui Dou; Lina Li; Chao Yan; Xiang Li (Journal of Environmental Management, 2025)

All-solid-waste-based non-sintered ceramsite prepared from coal fly ash and dechlorinated municipal solid waste incineration fly ash: performance and hydration mechanisms - Kai Xu; Xinyuan Zhan; Yan Wang; Jie Wang; Rui Deng; Rui Wang; Chen Li; Shui Jiang; Xiaomoli Li; Jingyu Li; Yuxi Zhang (Journal of Environmental Management, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Quantifying nitrogen loss responses to seasonal deluges and droughts: A modeling study in a subtropical agro-forest catchment, upper Yangtze River - Wei Zhang; Xunhua Zheng; Siqi Li; Chunyan Liu; Zhisheng Yao; Shenghui Han; Rui Wang; Kai Wang; Bo Zhu; Minghua Zhou; Xiao Chen; Yong Li (Ecohydrology & Hydrobiology, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Agricultural plastic Legacy in river Sediments: Abundance, oxidation, and occurrence characteristics of microplastics across rural China - Ge Ma; Kuangjia Li; Wei Zou; Rui Xin; Xiaohan Zhang; Jiaojiao Feng; Zheng Chen; Yinan Yang; Xiaomeng Lou; Kai Zhang; Fengxia Yang (Environmental Pollution, 2025)

Phytosphingosine suppresses gastric cancer through SFRP4/β-catenin axis-mediated Wnt signaling pathway inhibition - Yanchen Liu; Rui Guo; Chi Xue; Xinwei Zhang; Fanghao Xiao; Xiangxuan Zhao; Zhi Zhu; Kai Li (Chemico-Biological Interactions, 2025)

Greenhouse Gas Footprints of Maize Cultivation Systems in Different Climate Zones: Field Data Validation and Application of CNMM–DNDC as a Hydro-Biogeochemical Model - Siqi Li; Wei Zhang; Yong Li; Chunyan Liu; Bo Zhu; Job Kihara; Peter Bolo; Zhisheng Yao; Kai Wang; Shenghui Han; Rui Wang; Jiarui Sun; et al. (Advances in Atmospheric Sciences, 2025)

MicroScale thermophoresis (MST): precise analysis of molecular interactions in plants - Shi-Kai Cao; Hewei Du; Yu Li; Jianhua Zhang; Rui Liu (Trends in Plant Science, 2025)

Hydrological variability significantly influences aquatic biological integrity at the spatial scale in semi-arid watersheds - Lina Li; Rui Xia; Xinghui Xia; Ming Dou; Minhua Ling; Yan Chen; Jinghui Dou; Kai Zhang; Ruining Jia; Chao Yan (Journal of Hydrology, 2025)

Impact of amplicon length on the identification of edible oils based on real-time PCR - Kai Chen; Bin Xiao; JianZhi Luo; XueWei Yuan; Juan Zhang; Songxue Wang; Rui Zhang; Nan Wang; LiQiang Liu; AiKe Li; Ailiang Chen (Food Control, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Ontology-driven knowledge graph for decision-making in resilience enhancement of underground structures: Framework and application - Bin-Lin Gan; Dong-Mei Zhang; Zhong-Kai Huang; Fei-Yu Zheng; Rui Zhu; Wei Zhang (Tunnelling and Underground Space Technology, 2025)

Efficient solar-driven tandem catalysis for biomass valorization: selective C C bond cleavage to synthesize xylitol - Liangdong Hu; Huiyan Zhang; Zupeng Chen; Nengchao Luo; Lian-Hua Xu; Kai Wu; Longfei Hong; Sheng Chu; Rui Xiao (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Extreme rainfall drives the shift in dominant water quality “Sink” from forest land to grassland in the Yellow River Basin - Jinghui Dou; Rui Xia; Xinghui Xia; Xiaohui Jiang; Kai Zhang; Yan Chen; Lina Li; Chao Yan (Journal of Hydrology, 2025)

Mechanistic insights into electric field-driven specific ion effects on nanoplastics aggregation in heavy metal co-contaminated aquatic systems - Yan Peng; Rui Li; Ying Tang; Xinmin Liu; Yaowu Zhang; Xinping Gao; Kai Wang; Rui Tian; Hang Li (Journal of Hazardous Materials, 2025)

Impacts on structure, lipase-inhibitory activity, and digestive characters of fermented coconut protein with Lactobacillus strains - Yufang Tian; Tao Lin; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Elham Azarpazhooh; Marjan Ajami; Ghahvechi Chaeipeima Masha; Xin Rui; Wei Li (Food Bioscience, 2025)

Tart cherry extract alleviates gouty inflammatory response by down-regulating NF-κB signaling pathway - En Shi; Rui Wang; Lingfang Xu; Haijing Wang; Maichao Li; Kai Guo; Feng Zhang; Bingjie Liu; Yuwei He; Xianghong Meng (Food Bioscience, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Tailoring reactivity in MOF derivatives via thermally induced amorphization: Synergistic crystalline/amorphous heterointerfaces for efficient 4-nitrophenol detoxification - Wenyao Zhang; Mian Wang; Rui Xiong; Kai Wei; Genping Zhu; Wei Ye; Wei Wang; Haijiao Xie; Peng Gao; Gan Jia (Chemical Engineering Journal, 2025)

Phylogenetic and toxicogenomic profiling of CYPomes to elucidate convergent and divergent insecticide resistance profiles in three rice planthopper species - Kai Lin; Hongxin Wu; Zhongsheng Li; Zichun Zhong; Liuyan He; Yujing Guo; Jie Zhang; Xiaoxia Xu; Wenqing Zhang; Fengliang Jin; Rui Pang (Journal of Pest Science, 2025)

Satellite-Based Analysis of Nutrient Dynamics in Northern South China Sea Marine Ranching Under the Combined Effects of Climate Warming and Anthropogenic Activities - Rui Zhang; Nanyang Chu; Kai Yin; Langsheng Dong; Qihang Li; Huapeng Liu (Journal of Marine Science and Engineering, 2025)
This study presents a comprehensive assessment of long-term nutrient dynamics in the northern South China Sea (NSCS), a region that hosts the world’s largest marine ranching cluster and serves as a cornerstone of China’s “Blue Granary” initiative. By integrating multi-sensor satellite remote sensing data (Landsat and Sentinel-2, 2002–2024) with in situ observations, we developed robust retrieval algorithms for total nitrogen (TN) and total phosphorus (TP), achieving high accuracy (TN: R2 = 0.82, RMSE = 0.09 mg/L; TP: R2 = 0.94, RMSE = 0.0071 mg/L; n = 63). Results showed that TP concentrations increased significantly faster than TN, leading to a decline in the TN:TP ratio (NP) from 19.2 to 13.2 since 2013. This shift indicates a transition from phosphorus (P) limitation to nitrogen (N) limitation, driven by warming sea surface temperatures (SST) (about 1.16 °C increase) and increased anthropogenic phosphorus inputs (about 27.84% increase). The satellite-based framework offers a scalable, cost-effective solution for monitoring aquaculture water quality. When integrated with artificial intelligence (AI) technologies, these near-real-time nutrient anomaly data can support early warning of harmful algal blooms (HABs), offering key insights for ecosystem-based management and climate adaptation. Overall, our findings highlight the utility of remote sensing in advancing sustainable marine resource governance amid environmental change.

Probabilistic analysis of fire casualties in an urban traffic tunnel considering the uncertainty of vehicle queue - Dong-Mei Zhang; Rui Zhu; Zhong-Kai Huang; Lei Yu (Tunnelling and Underground Space Technology, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

Modelling forest-atmosphere exchanges of carbon and water using an improved hydro-biogeochemical model in subtropical and temperate monsoon climates - Wei Zhang; Xunhua Zheng; Siqi Li; Shenghui Han; Chunyan Liu; Zhisheng Yao; Rui Wang; Kai Wang; Xiao Chen; Guirui Yu; Zhi Chen; Jiabing Wu; et al. (Ecological Modelling, 2025)

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

An oral recombinant human type 5 adenovirus vector vaccine encoding the S protein of Type I feline coronavirus effectively protection against FCoV challenge in cats - Gu-nan Deng; Chang-zhan Xie; Ke-lei Zhou; Chun-sai He; Yuan-Zhen Ma; A.-jia Ake; Rui Guo; Kai Li; Chen Peng; Bin Zhang (Veterinary Microbiology, 2025)

Traffic-based resilience assessment on urban road tunnel affected by fire accident - Rui Zhu; Dong-Mei Zhang; Zhong-Kai Huang; Xiao-yang Guo; Bin-lin Gan; Wen-ding Zhou (Tunnelling and Underground Space Technology, 2025)

Investigation of aerodynamic performance and operational optimization of wing sails at varying spacings - Rui Zhang; Lianzhong Huang; Guisheng Peng; Zhang Ruan; Ranqi Ma; Kai Wang; Jianlin Cao; Jianyi Wu; Xiaowu Li (Ocean Engineering, 2025)

Adaptive online modeling of ship maneuvering based on multiscale convolutional hybrid SRU models - Haoyang Zhao; Lianzhong Huang; Ranqi Ma; Kai Wang; Jianlin Cao; Tiancheng Wang; Zhang Ruan; Rui Zhang; Yingbo Zang; Weiping Li; Xiangjun Chen (Ocean Engineering, 2025)

Aluminum and microplastic release from reflective agricultural films disrupt microbial communities and functions in soil - Kai Wang; Markus Flury; Yakov Kuzyakov; Hao Zhang; Wei Zhu; Rui Jiang (Journal of Hazardous Materials, 2025)

Improving the microenvironment of tracking photovoltaic systems promotes soil organic carbon accumulation by mediating plant carbon inputs and microbial necromass retention - Siqi Zhang; Jirui Gong; Rui Wang; Kai Zheng; Weiyuan Zhang; Xuede Dong; Yuxia Hu; Guisen Yang; Chenyi Yan; Shangpeng Zhang; Ruijing Wang; Tong Wang (Journal of Environmental Management, 2025)

Potentially toxic elements in sediments of China's Shihe River: Urban-agricultural impact assessment and source apportionment - Kai Zhang; Ge Ma; Zheng Chen; Jilu Wang; Xiaomeng Lou; Yinan Yang; Jiaojiao Feng; Fengxia Yang; Kuangjia Li; Chenxuan Shang; Rui Xin; Xiangmin Zhang (Journal of Contaminant Hydrology, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

In situ synthesized carbon quantum dots@metal organic framework via corroding Ni foam for efficient oxygen evolution reaction - Yuzhen Zhang; Huajun Zhou; Peihua Zhao; Kai Yuan; Rui Zhou; Hui Gao; Yongping Qu; Yanzhong Wang (Fuel, 2025)

Amelioration of Kluyveromyces marxianus GY-8 on high-fat diet-induced obesity and gut microbiota dysbiosis - Nanyu Tang; Xiaogan Zhao; Tao Lin; Yihan Lin; Chang Xu; Kai Ma; Changliang Zhang; Feng Ji; Ghahvechi Chaeipeima Mahsa; Luyao Xiao; Xin Rui; Wei Li (Food Bioscience, 2025)

Enhanced gut damage and microbial imbalance in bullfrog tadpoles (Lithobates catesbeiana) exposed to polystyrene microplastics under high-temperature conditions - Zhilong Wang; Jun Xie; Guangjun Wang; Huirong Yang; Zhifei Li; Kai Zhang; Rui Shu; Wenping Xie; Jingjing Tian; Hongyan Li; Wangbao Gong; Yun Xia (Environmental Pollution, 2025)

Sex-Specific Association Between Urinary Metal and Serum Homocysteine Levels in Chinese Older Adults: A Study Based on the Yinchuan Community-Dwelling Elderly Cohort - Zhongyuan Zhang; Kai Wang; Siyu Duan; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Pei He; Rui Wang; ZeYang Bai; JinHao Jia; Limeng Xiong; Xiaoyu Li; et al. (Exposure and Health, 2025)

Ecological security and structural optimization of land space in the Pearl River Delta Urban Agglomeration: an approach based on the footprint family - Cong Huang; Jun Liu; Hanyu Yin; Zhonghao Zhang; Wei Cao; Wenfang Tan; Xufeng Fei; Chen Xu; Lumeng Liu; Jiali Chen; Kai Li; Rui Xiao (Environment, Development and Sustainability, 2025)

In-field degradation of polybutylene adipate-co-terephthalate (PBAT) films, microplastic formation, and impacts on soil health - Kai Wang; Markus Flury; Shiyan Sun; Junling Cai; Aihua Zhang; Qiang Li; Rui Jiang (Environmental Research, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Gridemis V2.0: A highly integrated algorithm scheme for high-resolution and multi-component allocation of emission inventories used in air quality models - Chuanda Wang; Wenjiao Duan; Shuiyuan Cheng; Xiaosong Hou; Junfeng Zhang; Yu Wang; Hanyu Zhang; Kai Wang; Rui Liu (Environmental Modelling & Software, 2025)

Solar-driven transient Lewis acid sites for synergistic efficient photocatalytic isomerization of glyceraldehyde - Liangdong Hu; Lian-hua Xu; Chenjun Yang; Longfei Hong; Kai Wu; Sheng Chu; Longlong Ma; Shurong Wang; Rui Xiao; Huiyan Zhang (Chemical Engineering Journal, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

In-situ surface reconstruction of BiVO4/CuFe2O4 photoanode for efficient and robust solar water oxidation - Tengfei Wang; Kai Song; Houjiang Liu; Hongyan Li; Yufei Zhang; Weijie Ren; Rui Zhang; Kun Li; Fang He; Zhenxing Qin; Huilin Hou (Chemical Engineering Journal, 2025)

Omics research in atherosclerosis - Kai-Jiang Tian; Yu Yang; Guo-Shuai Chen; Nian-hua Deng; Zhen Tian; Rui Bai; Fan Zhang; Zhi-Sheng Jiang (Molecular and Cellular Biochemistry, 2025)

Facile synthesis of high-swelling cyclodextrin polymer for sustainable water purification - Kai Zhang; Yu Dai; Rui Liu; Yongli Shi; Guofei Dai; Fan Xia; Xiaojin Zhang (Journal of Hazardous Materials, 2025)

Chemical characteristics and sources apportionment of volatile organic compounds in the primary urban area of Shijiazhuang, North China Plain - Xiao Zhang; Junfeng Wang; Jiangwei Zhao; Junliang He; Yali Lei; Kai Meng; Rui Wei; Xue Zhang; Miaomiao Zhang; Shuangying Ni; Eleonora Aruffo (Journal of Environmental Sciences, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Monitoring nutrient and beneficial elements in the topsoil: the function of weathered background and later surficial process on their distribution - Bo Zhang; Kai-Ning Lv; Huan Li; Qin-Rui Zhang; Zhi-Qiang Yin; Wei-Zhi Zhou; Guo-Li Yuan (Environmental Monitoring and Assessment, 2025)

Transboundary cooperation potential under climate change and hydropower development in the Dulong-Irrawaddy river basin: A perspective on the water-energy-food-ecosystem nexus - Ziyue Xu; Kai Ma; Jiwei Leng; Kaiwen Zhang; Rui Luo; Daming He (Journal of Cleaner Production, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Boosting internal accessibility via 50-nm-diameter channels in NiO@nitrogen-containing carbon for high rate performance and high contribution of electric double layer capacitance - Kai Zhang; Rui Zhang; Qiguan Wang; Youjun Huang; Qiannan Liang; Guixin Wang; Yuxiao Hu; Ke Qin; Sumin Wang (Chemical Engineering Journal, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Landscape fragmentation of built-up land significantly impact on water quality in the Yellow River Basin - Jinghui Dou; Rui Xia; Kai Zhang; Chao Xu; Yan Chen; Xiaoyu Liu; Xikang Hou; Yingze Yin; Lina Li (Journal of Environmental Management, 2024)

Endogenous phosphorus release from plateau lakes responds significantly to temperature variability over the last 50 years - Chao Yan; Rui Xia; Yan Chen; Lixin Jiao; Xiaoyu Liu; Yingze Yin; Qiang Hu; Kai Zhang; Lina Li; Hao Liu (Journal of Environmental Management, 2024)

Janus membrane with oriented fiber structure for boosted personal wet-thermal management - Miaomiao Hu; Yiwen Yang; Kai Li; Yilong Zhang; Haozhen Dong; Yang Wang; Xiuqin Zhang; Rui Wang; Jing Wu (Chemical Engineering Journal, 2024)

TP53 to mediate immune escape in tumor microenvironment: an overview of the research progress - Kai-li Zhu; Fei Su; Jing-ru Yang; Ruo-wen Xiao; Rui-yue Wu; Meng-yue Cao; Xiao-ling Ling; Tao Zhang (Molecular Biology Reports, 2024)
Increasing evidence suggests that key cancer-causing driver genes continue to exert a sustained influence on the tumor microenvironment (TME), highlighting the importance of immunotherapeutic targeting of gene mutations in governing tumor progression. TP53 is a prominent tumor suppressor that encodes the p53 protein, which controls the initiation and progression of different tumor types. Wild-type p53 maintains cell homeostasis and genomic instability through complex pathways, and mutant p53 (Mut p53) promotes tumor occurrence and development by regulating the TME. To date, it has been wildly considered that TP53 is able to mediate tumor immune escape. Herein, we summarized the relationship between TP53 gene and tumors, discussed the mechanism of Mut p53 mediated tumor immune escape, and summarized the progress of applying p53 protein in immunotherapy. This study will provide a basic basis for further exploration of therapeutic strategies targeting p53 protein.

Method for Non-Contact Measuring the Weight of Sturgeon in Intensive Aquaculture - Junjie Hu; Kai Lin; Shiyu Zhang; Rui Zhang; Hongsong Li; Runqiu Xia (Fishes, 2024)
Weight information plays a pivotal role in sturgeon breeding and production management. However, manual measurement is time consuming and labor intensive due to the immense size of the sturgeon. Due to the unique body shape of the sturgeon, traditional image segmentation algorithms struggle to extract the necessary features from sturgeon images, which makes them unsuitable for this particular species. Moreover, accurately measuring weight in an occlusion environment is difficult. To address these challenges, an improved YOLOv5s model with a context augmentation module, focal-efficient intersection over union, and soft non-maximum suppression was proposed in this paper. To validate the model’s feasibility, the improved YOLOv5s model was first pre-trained using the sturgeon dataset, followed by further training on the occlusion dataset for segmentation tasks. Based on the phenotypic data obtained from the improved model, a multilayer perceptron method was used to estimate the sturgeon’s weight accurately. Experimental results demonstrated that the average precision of the improved YOLOv5s model reached 89.80% under occlusion conditions, and the correlation coefficient of noncontact weight measurement results reached 89.80%. The experimental results showed that the improved algorithm effectively performs segmentation of sturgeon in occlusion conditions and can accurately estimate the mass.

Dynamic nonparametric modeling of sail-assisted ship maneuvering motion based on GWO-KELM - Haoyang Zhao; Lianzhong Huang; Ranqi Ma; Kai Wang; Tiancheng Wang; Zhang Ruan; Rui Zhang; Baoshen Jiang; Xiaowu Li; Jianyi Wu (Ocean Engineering, 2024)

Granular insights into occupant behaviours and CO2 emissions in the UK - Ruiming Zhang; Tongyu Zhou; Rui Jing; Hua Cai; Tao Lin; Kai Wang; Huanye He; Guoqin Zhang; Xian Wu; Hong Ye (Journal of Cleaner Production, 2024)

Half-antibody spur one-to-one recognition mechanism can function with chemical-staining technology for next-generation lateral flow immunoassay - Jingke Xu; Jing Zhou; Kai Liu; Tong Bu; Leina Dou; Rui Shu; Sijie Liu; Shaochi Wang; Xuechi Yin; Daohong Zhang; Ruiling Zhang; Jie Cheng; et al. (Chemical Engineering Journal, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

A novel method of fuel consumption prediction for wing-diesel hybrid ships based on high-dimensional feature selection and improved blending ensemble learning method - Tian Lan; Lianzhong Huang; Ranqi Ma; Zhang Ruan; Shan Ma; Zhongwei Li; Haoyang Zhao; Cong Wang; Rui Zhang; Kai Wang (Ocean Engineering, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

Undrained face stability analysis of dual circular tunnels using three-dimensional adaptive lower bound finite element limit analysis method - Rui Sun; Junsheng Yang; Yunhuan Lan; Haibing Cai; Kai Zhang; Feng Yang (Computers and Geotechnics, 2024)

Numerical investigation on the effects of heel on the aerodynamic performance of wing sails - Rui Zhang; Lianzhong Huang; Ranqi Ma; Guisheng Peng; Zhang Ruan; Cong Wang; Haoyang Zhao; Boyang Li; Kai Wang (Ocean Engineering, 2024)

Tuning electronic environment of B sites in boron carbonitride nanoribbon boosts catalytic activity of reducing N2 to NH3 - Kai Zhang; Rui Zhang; Yuxin Cui; Jiayin Shang; Xueling Wei; Sumin Wang; Siqin Jia; Ke Qin; Haiyan Zhang; Hongyan Wang; Taotao Ai; Qiguan Wang (Fuel, 2024)

Highly selective and sensitive immunoassays for flurogestone acetate analysis in goat milk: From rational hapten design and antibody production to assay development - Rui Liu; Xingya Sun; Yingjie Zhang; Peipei Li; Li Nan; Qing Shen; Kai Wen; Xuezhi Yu; Jianzhong Shen; Yantong Pan; Zhanhui Wang (Food Chemistry, 2024)

Gas chromatography-mass spectrometry and non-targeted metabolomics analysis reveals the flavor and nutritional metabolic differences of cow's milk fermented by Lactiplantibacillus plantarum with different phenotypic - Xueliang Zhang; Changliang Zhang; Luyao Xiao; Xiaochan Wang; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Bioscience, 2024)

Promotion and monitor wound healing by anthocyanin enhanced light curing ε-poly-l-lysine hydrogel encapsulated Cu-MOF - Xiawei Zhao; Rui Liu; Tiantian Tang; Zihao Liu; Xiaozhi Liu; Kai Yu; Ye Zhang; Hao Wang (Chemical Engineering Journal, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Biodegradable film mulching increases soil microbial network complexity and decreases nitrogen-cycling gene abundance - Hao Zhang; Duntao Shu; Jiaqi Zhang; Xuejun Liu; Kai Wang; Rui Jiang (Science of The Total Environment, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

A novel cooperative optimization method of course and speed for wing-diesel hybrid ship based on improved A* algorithm - Cong Wang; Lianzhong Huang; Ranqi Ma; Kai Wang; Jinlu Sheng; Zhang Ruan; Yu Hua; Rui Zhang (Ocean Engineering, 2024)

Simultaneous biogas upgrading and single cell protein production using hydrogen oxidizing bacteria - Rui Li; YuFeng Jiang; JieHua Huang; Kai Luo; XiaoLei Fan; RongBo Guo; Tao Liu; YiFeng Zhang; ShanFei Fu (Chemical Engineering Journal, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Comprehensive utilization for hydrothermal conversion products of food waste - Rui Bao; Shuzhong Wang; Jiaqi Feng; Kai Liu; Hui Liu; Fan Zhang; Yuanwang Duan; Zicheng Li; Jianqiao Yang (Journal of Cleaner Production, 2024)

Integrated machine learning reveals aquatic biological integrity patterns in semi-arid watersheds - Lina Li; Rui Xia; Ming Dou; Kai Zhang; Yan Chen; Ruining Jia; Xiaoxuan Li; Jinghui Dou; Xiang Li; Qiang Hu; Hui Zhang; Nixi Zhong; et al. (Journal of Environmental Management, 2024)

Parametric design and multi-objective optimization of daylight performance in gallery skylight systems: A case study on the high museum expansion - Kai Li; Hiroatsu Fukuda; Li Zhang; Rui Zhou (Energy and Buildings, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Genetic structure of ten Artemia populations from China: cumulative effects of ancient geological events, climatic changes, and human activities - Ke Li; Rui Zhang; Li-Ying Sui; Chi Zhang; Xue-Kai Han (Frontiers in Marine Science, 2024)
This study investigated the population genetics and distribution patterns of Artemia populations from ten inland salt lakes in China. A total of 1,274,698 Artemia single nucleotide polymorphisms (SNPs) were identified. The results showed that these populations could be geographically and genetically divided into four distinct groups, and that the Tibetan populations were further divided into two subpopulations with a trend of decreasing genetic diversity from west to east. The Tibetan population had the highest genetic diversity, whereas the Shanxi population had the lowest. There was moderate genetic differentiation between the Tibetan populations and greater genetic differentiation between the Xinjiang and Shanxi populations. IBD (isolation by distance) suggested that geographical isolation contributes to genetic differentiation. In addition, there was some degree of gene flow among the ten populations, with A. sinica showing unidirectional gene flow in all populations in the eastern Nagri region. Species distribution modeling showed that mean annual temperature, temperature seasonality, and annual precipitation were the main environmental factors affecting the distribution of Artemia populations and suitable habitats for Tibetan populations will be further reduced in the future. It is necessary to strengthen the protection of germplasm resources and formulate scientific protocols for the sustainable development and utilization of Artemia resources.

Carbazomycins I and J, two novel carbazole alkaloids isolated from Saccharopolyspora phattalungensis - Wen Wang; Er Juan Zhao; Ting Peng; Zhang Yuan Yan; Zhi Kai Guo; Rui Hua Jiao (Phytochemistry Letters, 2024)

Novel optimized layout for Flettner rotors based on reuse of wake energy - Rui Zhang; Lianzhong Huang; Kai Wang; Ranqi Ma; Zhang Ruan; Cong Wang (Journal of Cleaner Production, 2024)

Recovery hydrotalcite from neutralization sludge of acid mine drainage with high manganese for degradation of norfloxacin with activated peroxymonosulfate - Qingsheng Xu; Zhengbo Yue; Rui Deng; Kang Su; Xin Chuai; Kai Zhang; Jin Wang (Chemical Engineering Journal, 2024)

Occurrence characteristics and influencing factors of antibiotic resistance genes in rural groundwater in Henan Province - Kai Zhang; Kuangjia Li; Feiyue Hu; Rui Xin; Penglin Fan; Yarou Lu; Ningning Wang; Mengyuan Qin; Ruojing Li (Environmental Science and Pollution Research, 2024)

Spatial and temporal variation in lake macroinvertebrate communities is decreased by eutrophication - Rui Dong; Kai Peng; Qingji Zhang; Jani Heino; Yongjiu Cai; Zhijun Gong (Environmental Research, 2024)

Effects of drought stress on seed germination and early seeding growth in Ferula ferulaeoides (Steud.) Korov. - Ying Ma; Kai Liao; Yun Zhu; Xin Lu; Kuan Wang; Xue Rui Zhang (Brazilian Journal of Botany, 2024)

Integrating photovoltaic noise barriers and electric vehicle charging stations for sustainable city transportation - Kai Zhang; Min Chen; Rui Zhu; Fan Zhang; Teng Zhong; Jian Lin; Linlin You; Guonian Lü; Jinyue Yan (Sustainable Cities and Society, 2024)

Investigation of the antimicrobial susceptibility patterns of marine cyanobacteria in Bohai Bay: Cyanobacteria may be important hosts of antibiotic resistance genes in marine environment - Rui Xin; Ying Zhang; Kai Zhang; Yichen Yang; Yongzheng Ma; Zhiguang Niu (Science of The Total Environment, 2024)

Emission characteristics of intermediate volatility organic compounds from a Chinese gasoline engine under varied operating conditions: Influence of fuel, velocity, torque, rotational speed, and after-treatment device - Rongzhi Tang; Song Guo; Kai Song; Ying Yu; Rui Tan; Hui Wang; Kefan Liu; Ruizhe Shen; Shiyi Chen; Limin Zeng; Zhou Zhang; Wenbin Zhang; et al. (Science of The Total Environment, 2024)

Selective solvent extraction of Cu(II) from aqueous solutions using an acyl-based thiourea: Extraction study and DFT analysis of reaction mechanism - Xiaoping Huang; Kai Jin; Ruyi Zhang; Yutao Gong; Jianxian Zeng; Rui Zhang; Yuan Liu; Jianrong Xue (Hydrometallurgy, 2024)

Effects of Lacticaseibacillus paracasei SNB-derived postbiotic components on intestinal barrier dysfunction and composition of gut microbiota - Luyao Xiao; Changliang Zhang; Xueliang Zhang; Xiaogan Zhao; Ghahvechi Chaeipeima Mahsa; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Research International, 2024)

Pixel-level regression for UAV hyperspectral images: Deep learning-based quantitative inverse of wheat stripe rust disease index - Jie Deng; Xunhe Zhang; Ziqian Yang; Congying Zhou; Rui Wang; Kai Zhang; Xuan Lv; Lujia Yang; Zhifang Wang; Pengju Li; Zhanhong Ma (Computers and Electronics in Agriculture, 2023)

Direct regeneration of spent LiFePO4 materials via a green and economical one-step hydrothermal process - Jinyi Yang; Kai Zhou; Rui Gong; Qi Meng; Yingjie Zhang; Peng Dong (Journal of Environmental Management, 2023)

The interaction among Kluyveromyces marxianus G-Y4, Lacticaseibacillus paracasei GL1, and Lactobacillus helveticus SNA12 and signaling molecule AI-2 participate in the formation of biofilm - Xiaomeng Wang; Kai Ma; Changliang Zhang; Feng Ji; Lili Chen; Xueliang Zhang; Ghahvechi Chaeipeima Mahsa; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Microbiology, 2023)

A novel method of desynchronized operation of sails for ship wind-assisted propulsion system - Rui Zhang; Lianzhong Huang; Guisheng Peng; Ranqi Ma; Kai Wang; Feng Tian; Qiushi Song (Ocean Engineering, 2023)

Strategies for enhancing performance of perovskite bismuth ferrite photocatalysts (BiFeO3): A comprehensive review - Tianhong Zhou; Tianjiao Zhai; Huidong Shen; Jinyi Wang; Rui Min; Kai Ma; Guozhen Zhang (Chemosphere, 2023)

Flow backward alleviated the river algal blooms - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Process and mechanism of recovering layered double hydroxides (LDHs) from acid mine drainage (AMD) and synergetic removal of manganese - Qingsheng Xu; Zhengbo Yue; Rui Deng; Xinquan Wang; Xin Chuai; Kai Zhang; Jin Wang (Journal of Environmental Chemical Engineering, 2023)

Effects of Lactiplantibacillus plantarum with different phenotypic features on the nutrition, flavor, gel properties, and digestion of fermented soymilk - Xueliang Zhang; Changliang Zhang; Luyao Xiao; Suying Wang; Xiaochan Wang; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Bioscience, 2023)

Polyamide/UiO-66-NH2 nanocomposite membranes by polyphenol interfacial engineering for molybdenum(VI) removal - Zhenwei Wu; Jianxian Zeng; Zhengqiu Yuan; Rui Zhang; Xiaoping Huang; Fan Feng; Minjuan Chen; Kai Jin; Shengkai Yang; Yahong Li (Desalination, 2023)

Flat-leaf submerged plants are more sensitive to invasion intensity and water nutrition levels than needle-leaf ones - Yi-Luan Shen; Shu-Yu Zhang; Xiao-Fei Yuan; Kai Sun; Jing-Fang Cai; Jing-Jing Xue; Yu Zhang; Si-Ha A; Li-Juan Yang; Rui Cheng; Hong-Li Li; Guang-Chun Lei (Hydrobiologia, 2023)

Holocene climatic controls on flooding regime along the Ussuri River in Northeast Asia - Zhenqing Zhang; Lin Li; Rui Yin; Lu Zhang; Kai Yi; He Ji; Haijiao Yin; Lili Huo (Science of The Total Environment, 2023)

Controlled release of Lactiplantibacillus plantarum by colon-targeted adhesive pectin microspheres: Effects of pectin methyl esterification degrees - Danling Xu; Xiaogan Zhao; Ghahvechi Chaeipeima Mahsa; Kai Ma; Changliang Zhang; Xin Rui; Mingsheng Dong; Wei Li (Carbohydrate Polymers, 2023)

Co-cultivation effects of Lactobacillus helveticus SNA12 and Kluveromyces marxiensis GY1 on the probiotic properties, flavor, and digestion in fermented milk - Xiaomeng Wang; Wenpei Li; Ghahvechi Chaeipeima Mahsa; Changliang Zhang; Kai Ma; Xin Rui; Wei Li (Food Research International, 2023)

A sulfonate-functionalized covalent organic framework for record-high adsorption and effective separation of organic dyes - Rui Li; Xihao Tang; Jialin Wu; Kai Zhang; Qianni Zhang; Jiaqi Wang; Jiayue Zheng; Shengrun Zheng; Jun Fan; Weiguang Zhang; Xinle Li; Songliang Cai (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Distribution and risk assessment of microplastics in Liujiaxia Reservoir on the upper Yellow River - Rui Min; Kai Ma; Hongwei Zhang; Jiaqian Zhang; Siyi Yang; Tianhong Zhou; Guozhen Zhang (Chemosphere, 2023)

Phosphorus – The main limiting factor in riverine ecosystems in China - Yan Chen; Jie Chen; Rui Xia; Wenpan Li; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2023)

A novel energy harvest method based on the vortex-induced vibration of a circular cylinder in a confined channel for the self-powered buoy - Rui Zhang; Lianzhong Huang; Kai Wang; Ranqi Ma; Boyang Li; Baoshou Zhang (Ocean Engineering, 2023)

Inhibition of human sulfotransferases (SULTs) by per- and polyfluoroalkyl substances (PFASs) and structure-activity relationship - Yong-Zhe Liu; Kai Yang; Wei Zhang; Qian zhang; Tong-Feng Liu; Tong Xu; Yang Li; Rui-Xue Ran; Kun Yang; Yun-Feng Cao; Zhong-Ze Fang (Food and Chemical Toxicology, 2023)

Determination of Rock Mass Parameters for the RHT Model Based on the Hoek–Brown Criterion - Shenglin Li; Tianlong Ling; Dianshu Liu; Shufeng Liang; Rui Zhang; Bo Huang; Kai Liu (Rock Mechanics and Rock Engineering, 2023)

Full genome sequence of a novel iflavirus from the aster leafhopper Macrosteles fascifrons - Jiajing Xiao; Kai Zhu; Rui Ma; Chunmin Zhang; Keliang Lv; Danfeng Ge; Renyi Liu (Virus Genes, 2023)

Metagenomic insights into bacterial communities and functional genes associated with texture characteristics of Kazakh artisanal fermented milk Ayran in Xinjiang, China - Malina Kuerman; Rui Wang; Yu Zhou; Xiaoying Tian; Qingyu Cui; Huaxi Yi; Pimin Gong; Zhe Zhang; Kai Lin; Tongjie Liu; Lanwei Zhang (Food Research International, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Secondary organic aerosol formation in China from urban-lifestyle sources: Vehicle exhaust and cooking emission - Zirui Zhang; Wenfei Zhu; Min Hu; Hui Wang; Lizi Tang; Shuya Hu; Ruizhe Shen; Ying Yu; Kai Song; Rui Tan; Zheng Chen; Shiyi Chen; et al. (Science of The Total Environment, 2023)

Lead-chlorine synergistic immobilization mechanism in municipal solid waste incineration fly ash (MSWIFA)-based magnesium potassium phosphate cement - Xing Cao; Qiushi Zhang; Weichen Yang; Lin Fang; Shiwei Liu; Rui Ma; Kai Guo; Ning Ma (Journal of Hazardous Materials, 2023)

Bluff-body MILD combustion regime for semicoke and bituminous coal mixtures with effect of oxidizer O2 concentration in O2/N2 and oxy-fuel (O2/CO2) atmospheres - Liutao Sun; Kai Xie; Rui Sun; Zewu Zhang; Yonghong Yan; Mengfan Yuan; Jiangquan Wu (Fuel, 2023)

Combining a novel biofilm reactor with a constructed wetland for rural, decentralized wastewater treatment - Rui Zhang; Xianchang Liu; Lutian Wang; Pan Xu; Kai Li; Xiaoxiao Chen; Rong Meng; Yuewu Pu; Xuetong Yang; Diederik P.L. Rousseau; Stijn W.H. Van Hulle (Chemical Engineering Journal, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Leakage Fault Diagnosis of Lifting and Lowering Hydraulic System of Wing-Assisted Ships Based on WPT-SVM - Ranqi Ma; Haoyang Zhao; Kai Wang; Rui Zhang; Yu Hua; Baoshen Jiang; Feng Tian; Zhang Ruan; Hao Wang; Lianzhong Huang (Journal of Marine Science and Engineering, 2022)
Wing-assisted technology is an effective way to reduce emissions and promote the decarbonization of the shipping industry. The lifting and lowering of wing-sail is usually driven by hydraulic system. Leakage, as an important failure form, directly affects the safety as well as the functioning of hydraulic system. To increase the system reliability and improve the wing-assisted effect, it is essential to conduct leakage fault diagnosis of lifting and lowering hydraulic system. In this paper, an AMESim simulation model of lifting and lowering hydraulic system of a Very Large Crude Carrier (VLCC) is established to analyze the operation characteristics of the hydraulic system. The effectiveness of the model is verified by the operation data of the actual hydraulic system. On this basis, a wavelet packet transform (WPT)-based sensitive feature extracting method of leakage fault for the hydraulic system is proposed. Subsequently, a support vector machine (SVM)-based multi-classification model and diagnosis method of leakage fault are proposed. The study results show that the proposed method has an accuracy of as high as 97.5% for six leakage fault modes. It is of great significance for ensuring the reliability of the wing-sail operation and improving the utilization rate of the offshore wind resources.

MCPIP1 alleviated alcohol-induced immune dysfunction via the MAPK/ERK signaling pathway - Yanjie Shen; Kai Zhang; Rui Wang; Shuaichen Sun; Yating Yang; Yitan Yao; Huanzhong Liu; Zhenhua Ren (Psychopharmacology, 2022)

Associations of exposure to lead and cadmium with risk of all-cause and cardiovascular disease mortality among patients with type 2 diabetes - Kai Zhu; Yuge Zhang; Qi Lu; Tingting Geng; Rui Li; Zhenzhen Wan; Xuena Zhang; Yujie Liu; Lin Li; Zixin Qiu; Meian He; Liegang Liu; et al. (Environmental Science and Pollution Research, 2022)

Monitoring glaciers in the Chenab basin with SBAS InSAR technology - Yue-kai Ding; Rui Liu; Yi-fei Fan; Ling-xiang Zhou; Qin Ji; Hong Zhang; Zuo-lin Xiao (Journal of Mountain Science, 2022)

Temporal Dynamics in Energy Fluxes and Trophic Structure of a Portunus trituberculatus Polyculture Ecosystem During Different Culture Periods - Jie Feng; Xiang-Li Tian; Shuang-Lin Dong; Rui-Peng He; Kai Zhang; Dong-Xu Zhang; Qing-Qi Zhang (Frontiers in Marine Science, 2022)
Swimming crab ( Portunus trituberculatus ) are an important aquaculture species in eastern coastal areas of China. To improve the understanding of P. trituberculatus culture ecosystem functioning, the dynamics of energy flow and trophic structure of a P. trituberculatus polyculture system (co-culture with white shrimp Litopenaeus vannamei and short-necked clam Ruditapes philippinarum ) were investigated in this study. Three Ecopath models representing the early, middle, and late culture periods of a P. trituberculatus polyculture ecosystem, respectively, were constructed to compare ecosystem traits at different culture periods. The results demonstrated that detritus was the main energy source in this polyculture ecosystem, and most of the total system throughput occurred at trophic levels I and II. Artificial food input and consumption by the culture organisms increased from early to middle and late periods, which produced marked impacts on biomass structure and primary production. R. philippinarum was considered to have a dominant influence on phytoplankton community dynamics which changed from nano- to pico-phytoplankton predominance, from the middle to the late period. Considering the low utilization efficiency of pico-phytoplankton production, large amounts of detritus accumulated in the sediment in the late period, which may constitute a potential risk for the ecosystem. Ecological network analyses indicated that the total energy flow and level of system organization increased from the early to the middle and late periods, whereas food web complexity and system resilience decreased from early to middle and late periods, which may indicate a trend of decreasing ecosystem stability. The system may be further optimized by increased stocking density of R. philippinarum and by introducing macro-algae at a suitable biomass to increase ecosystem stability, energy utilization efficiency, and aquaculture production.

Antibiotic resistomes in water supply reservoirs sediments of central China: main biotic drivers and distribution pattern - Kai Zhang; Kuangjia Li; Rui Xin; Ya Han; Ziwei Guo; Wei Zou; Wei Wei; Xiangchao Cui; Zhongshuai Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Cytotoxic α-pyrone derivatives from Cryptocarya yunnanensis - Qian He; Yue Fan; Yu Liu; Yun-Xia You; Li Rao; Yu Su; You-Kai Xu; Bin Lin; Chuan-Rui Zhang (Natural Product Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Overexpression of SoACLA-1 Gene Confers Drought Tolerance Improvement in Sugarcane - Kai Zhu; Chan Huang; Thi-Thu Phan; Li-Tao Yang; Bao-Qing Zhang; Yong-Xiu Xing; Yang-Rui Li (Plant Molecular Biology Reporter, 2021)

Coupling loss characteristics of N-P-C through runoff and sediment in the hilly region of SE China under simulated rainfall - Longzhou Deng; Tianyu Sun; Kai Fei; Liping Zhang; Xiaojuan Fan; Yanhong Wu; Liang Ni; Rui Sun (Environmental Science and Pollution Research, 2021)

Chlorogenic acid induces ROS-dependent apoptosis in Fusarium fujikuroi and decreases the postharvest rot of cherry tomato - Kai Kai; Rui Wang; Wanling Bi; Zhitao Ma; Wei Shi; Yingwang Ye; Danfeng Zhang (World Journal of Microbiology and Biotechnology, 2021)

Application of DNA barcoding and metabarcoding for species identification in salmon products - Nan Wang; Ran-Ran Xing; Meng-Yue Zhou; Rui-Xue Sun; Jian-Xun Han; Jiu-Kai Zhang; Wen-Jie Zheng; Ying Chen (Food Additives & Contaminants: Part A, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Geochemistry and zircon U-Pb ages of the Oligocene sediments in the Baiyun Sag, Zhujiang River Mouth Basin - Rui Sun; Ming Ma; Kai Zhong; Xiayang Wang; Zhao Zhao; Shuai Guo; Xingzong Yao; Gongcheng Zhang (Acta Oceanologica Sinica, 2021)

FoxO directly regulates the expression of TOR/S6K and vitellogenin to modulate the fecundity of the brown planthopper - Yi Dong; Weiwen Chen; Kui Kang; Rui Pang; Yipei Dong; Kai Liu; Wenqing Zhang (Science China Life Sciences, 2021)

Cenozoic tectonics and landform evolution in the Qilian Mountains and adjacent areas - Kai Du; Lirong Yang; Rui Zhang; Leping Yue; Huaijun Guo; Yunxiang Zhang; Jianxing Li; Hujun Gong (International Geology Review, 2020)

Evaluation on activation energy of deposited clay based on thermo-gravimetric analysis (TGA) and four kinetics models - Rui-xin Yan; Jian-bing Peng; Yan-jun Shen; Yu-liang Zhang; Lin-jun Gu; Shao-kai Wang (Bulletin of Engineering Geology and the Environment, 2020)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Aspergilolide, a steroid lactone produced by an endophytic fungus Aspergillus sp . MBL1612 isolated from Paeonia ostii - Pei-Liang Zhang; Gang Wang; Feng-Qing Xu; Jin-Song Liu; Ju-Tao Wang; Rui Zhang; Hai-Tao Liu; Jiang-Miao Hu; Guo-Kai Wang; Pei-Yun Wu (Natural Product Research, 2019)

Comparison of levofloxacin-based prophylaxis regimens for transrectal prostate biopsy: a prospective randomized single-center study - Rui Su; Kai-yun Wang; Dong Zhang; Ze-jun Yan; Jun-hui Jiang; Qi Ma (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Increasing grassland degradation stimulates the non-growing season CO2 emissions from an alpine meadow on the Qinghai–Tibetan Plateau - Lei Ma; Zhisheng Yao; Xunhua Zheng; Han Zhang; Kai Wang; Bo Zhu; Rui Wang; Wei Zhang; Chunyan Liu (Environmental Science and Pollution Research, 2018)

Joint inversion of GNSS and teleseismic data for the rupture process of the 2017 Mw6.5 Jiuzhaigou, China, earthquake - Qi Li; Kai Tan; Dong Zhen Wang; Bin Zhao; Rui Zhang; Yu Li; Yu Jie Qi (Journal of Seismology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Precipitation drives the biogeographic distribution of soil fungal community in Inner Mongolian temperate grasslands - Di Wang; Yichao Rui; Kai Ding; Xiaoyong Cui; Yanbin Hao; Li Tang; Zhe Pang; Biao Zhang; Shutong Zhou; Kui Wang; Yanfen Wang (Journal of Soils and Sediments, 2018)

Development and characterization of 32 SNP markers for the northern snakehead (Channa argus) using high resolution melting (HRM) - Bo-Chi Zhang; Gui-Rong Zhang; Wei Ji; Rui-Bin Yang; Gui-Wei Zou; Kun-Ci Chen; Kai-Jian Wei; Jonathan P. A. Gardner (Conservation Genetics Resources, 2017)

Influence of Inoculation of Leifsonia xyli subsp. xyli on Photosynthetic Parameters and Activities of Defense Enzymes in Sugarcane - Xiao-Qiu Zhang; Yong-Jian Liang; Kai Zhu; Chao-Xing Wu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Paleogene-Neogene stratigraphic realm and tectonic-sedimentary evolution of the Qilian Mountains and their surrounding areas - LiRong Yang; JianXing Li; LePing Yue; HongLiang Wang; HuaiJun Guo; XiaoHui Zhu; Tao Zhu; Kai Du; Rui Zhang; YunXiang Zhang; HuJun Gong (Science China Earth Sciences, 2017)

Suppressing Receptor-Interacting Protein 140: a New Sight for Salidroside to Treat Cerebral Ischemia - Tong Chen; Zhanqiang Ma; Lingpeng Zhu; Wenjiao Jiang; Tingting Wei; Rui Zhou; Fen Luo; Kai Zhang; Qiang Fu; Chunhua Ma; Tianhua Yan (Molecular Neurobiology, 2016)

Ectopic expression of UGT75D1, a glycosyltransferase preferring indole-3-butyric acid, modulates cotyledon development and stress tolerance in seed germination of Arabidopsis thaliana - Gui-Zhi Zhang; Shang-Hui Jin; Xiao-Yi Jiang; Rui-Rui Dong; Pan Li; Yan-Jie Li; Bing-Kai Hou (Plant Molecular Biology, 2016)

Molecular identification and expression of the Foxl2 gene during gonadal sex differentiation in northern snakehead Channa argus - Dan-Dan Wang; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Fish Physiology and Biochemistry, 2015)

Curcumin Promotes Cell Cycle Arrest and Inhibits Survival of Human Renal Cancer Cells by Negative Modulation of the PI3K/AKT Signaling Pathway - Hao Zhang; Weili Xu; Baolin Li; Kai Zhang; Yudong Wu; Haidong Xu; Junyong Wang; Jun Zhang; Rui Fan; Jinxing Wei (Cell Biochemistry and Biophysics, 2015)

Isolation and characterization of nineteen novel polymorphic microsatellite loci for the northern snakehead Channa argus - Ruo-Jin Yan; Kai-Jian Wei; Xiang-Zhao Guo; Gui-Rong Zhang; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Conservation Genetics Resources, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Development and characterization of 20 polymorphic microsatellite loci for the Lhasa schizothoracin Schizothorax waltoni - Xiang-Zhao Guo; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Rui-Bin Yang; Jonathan P. A. Gardner; Qi-Wei Wei (Conservation Genetics Resources, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Wave equation tomographic velocity inversion method based on the Born/Rytov approximation - Kai Zhang; Zheng Yin; Zhen-Chun Li; Yong-Rui Chen (Applied Geophysics, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Characterization of the Photosynthetic Apparatus and Proteome of Roseobacter denitrificans - Kai Tang; Rui Zong; Fan Zhang; Na Xiao; Nianzhi Jiao (Current Microbiology, 2010)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)